The present area of the Dniprovsky reservoirs - Vyshnevskyi, Viktor; Shevchuk, Sergii; Bondar, Andrii; Shevchenko, Iryna (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2017)
Having used the developed algorithm, a modern area of the Dnipro reservoirs has been established. The obtained area almost in all cases occurred much less than indicated in the reference sources.